Global control of bacterial nitrogen and carbon metabolism by a PTSNtr-regulated switch - Sánchez-Cañizares, C; Prell, J; Pini, F; Rutten, P; Kraxner, K; Wynands, B; Karunakaran, R; Poole, P (National Academy of Sciences, 2020)
The nitrogen-related phosphotransferase system (PTSNtr) of Rhizobium leguminosarum bv. viciae 3841 transfers phosphate from PEP via PtsP and NPr to two output regulators, ManX and PtsN. ManX controls central carbon metabolism via the tricarboxylic acid (TCA) cycle, while PtsN controls nitrogen uptake, exopolysaccharide production, and potassium homeostasis, each of which is critical for cellular adaptation and survival. Cellular nitrogen status modulates phosphorylation when glutamine, an abundant amino acid when nitrogen is available, binds to the GAF sensory domain of PtsP, preventing PtsP phosphorylation and subsequent modification of ManX and PtsN. Under nitrogen-rich, carbon-limiting conditions, unphosphorylated ManX stimulates the TCA cycle and carbon oxidation, while unphosphorylated PtsN stimulates potassium uptake. The effects are reversed with the phosphorylation of ManX and PtsN, occurring under nitrogen-limiting, carbon-rich conditions; phosphorylated PtsN triggers uptake and nitrogen metabolism, the TCA cycle and carbon oxidation are decreased, while carbon-storage polymers such as surface polysaccharide are increased. Deleting the GAF domain from PtsP makes cells “blind” to the cellular nitrogen status. PTSNtr constitutes a switch through which carbon and nitrogen metabolism are rapidly, and reversibly, regulated by protein:protein interactions. PTSNtr is widely conserved in proteobacteria, highlighting its global importance.